Prevalence of infections and antimicrobial use in the acute-care hospital setting in the Middle East: Results from the first point-prevalence survey in the region. (December 2020) - Alothman, Adel; Al Thaqafi, Abdulhakeem; Al Ansary, Adel; Zikri, Ahmed; Fayed, Akram; Khamis, Faryal; Al Salman, Jameela; Al Dabal, Laila; Khalife, Natasha; AlMusawi, Tariq; Alfouzan, Wadha; El Zein, Said; et al.
Highlights: This is the first Point-Prevalence Survey of infection in the Middle East. The overall point prevalence of infection was 28.3%. HAI and CAI point prevalence was 11.2% and 16.8%, respectively. The majority of patients with an infection (98.2%) received antimicrobial treatment. There were high levels of resistance to antimicrobials. Abstract: Objectives: Community-acquired (CAIs) and healthcare-associated (HAIs) infections are associated with significant morbidity and mortality. Data related to the epidemiology of these infections in the Middle East is scarce. The aim of this study is to estimate the prevalence of infections and antimicrobial use in the acute hospital setting in this region. Methods: A multicentre Point-Prevalence Survey was conducted in seven Middle Eastern countries: Egypt, Kingdom of Saudi Arabia, United Arab Emirates, Lebanon, Oman, Kuwait and Bahrain. Data were collected by the infection control and infectious diseases teams of the respective hospitals. Study surveys were completed in one day (03 April 2018). Results: The overall point prevalence of infection was 28.3%; HAI and CAI point prevalence was 11.2% and 16.8%, respectively. The majority of patients with an infection (98.2%) were receiving antimicrobial therapy. There were high levels of resistance to antimicrobials among Acinetobacter baumannii, Enterobacter cloacae, Klebsiella pneumoniae and other Klebsiella sp. Conclusions: Our findings indicate that the point prevalence of both HAI and CAI is high in a sample of Middle Eastern countries. These findings along with the increased use of antimicrobials represent a significant public health problem in the region; particularly in light of the growing regional antimicrobial resistance.